2004
DOI: 10.1111/j.1365-313x.2004.02066.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ASCORBATE PEROXIDASE 2 expression in wounded Arabidopsis leaves does not involve known wound‐signalling pathways but is associated with changes in photosynthesis

Abstract: Both laboratories equally participated in this work. SummaryASCORBATE PEROXIDASE 2 (APX2) encodes a key enzyme of the antioxidant network. In excess lightstressed Arabidopsis leaves, photosynthetic electron transport (PET), hydrogen peroxide (H 2 O 2 ) and abscisic acid (ABA) regulate APX2 expression. Wounded leaves showed low induction of APX2 expression, and when exposed to excess light, APX2 expression was increased synergistically. Signalling pathways dependent upon jasmonic acid (JA), chitosan and ABA wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 72 publications
5
99
1
2
Order By: Relevance
“…These results establish that ROS signaling from the chloroplast is central to the O 3 -induced oxidative stress response, as it has been shown to be for light and wound stress signaling (Fryer et al, 2002(Fryer et al, , 2003Chang et al, 2004). Analysis of gene expression profiles during the O 3 -induced oxidative stress response has revealed the coordinate upregulation and downregulation of genes coding for proteins that are targeted to and function in chloroplasts (Mahalingam et al, 2005).…”
Section: Intercellular Signaling In the Early Component Of The Oxidatmentioning
confidence: 88%
“…These results establish that ROS signaling from the chloroplast is central to the O 3 -induced oxidative stress response, as it has been shown to be for light and wound stress signaling (Fryer et al, 2002(Fryer et al, , 2003Chang et al, 2004). Analysis of gene expression profiles during the O 3 -induced oxidative stress response has revealed the coordinate upregulation and downregulation of genes coding for proteins that are targeted to and function in chloroplasts (Mahalingam et al, 2005).…”
Section: Intercellular Signaling In the Early Component Of The Oxidatmentioning
confidence: 88%
“…There is specific genetic evidence that H 2 O 2 generated by NADPH oxidases acts downstream of ABA in mediating stomatal closure (Zhang et al 2001;Kwak et al 2003;Bright et al 2006). H 2 O 2 may also be involved in signaling a variety of other hormone and stress responses (Chang et al 2004;Mori and Schroeder 2004;Shin and Schachtman 2004;Kwak et al 2006). Abitotic stress can cause many metabolic changes and is known to increase ROS levels in plant tissue Noctor 2003, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It follows that chloroplast-generated H 2 O 2 would represent a redox signal to activate cAPX expression in the nucleus. The initial induction observed under photooxidative stress conditions was related to the redox state of plastoquinone pool (see below for more details), whereas the subsequent mRNA accumulation was in line with continuous accumulation of H 2 O 2 (Yabuta et al, 2004 (Chang et al, 2004). This dye was shown to enhance the formation of singlet oxygen and hydrogen peroxide in chloroplasts, and the concomitant cAPX expression correlated with the methylviologen-generated H 2 O 2 accumulation in the cells.…”
Section: Plastid-generated Signals and Their Role In Nuclear Gene Expmentioning
confidence: 93%
“…Treating plants with H 2 O 2 was shown to induce the expression of nuclear genes related to plant responses to stress factors; thus, the expression of cAPX , the gene for cytoplasmic APX, is enhanced by excess light. The crucial role of hydrogen peroxide in cAPX expression was demonstrated in the experiments with Arabidopsis leaves infiltrated with catalase before excess light treatment: while the induction of APX2 (Arabidopsis cAPX) was inhibited, the expression of the superoxide dismutase gene was not affected (Chang et al, 2004). Recent studies of transgenic tobacco plants expressing the genes for catalase or thylakoidtype APX demonstrated that APX expression involved both hydrogen peroxide and the redox state of plastoquinone pool.…”
Section: Plastid-generated Signals and Their Role In Nuclear Gene Expmentioning
confidence: 98%